Causes of Employee Stress in a Production Organization (Journal of Universal Excellence, 2026)
Research Question (RQ): Do employees in manufacturing organizations experience stress on a daily basis? What are the causes of employee stress in production organizations? Who is responsible for creating stress among employees in production organizations? In what way can employees in production organizations take action against stress?Purpose: The purpose of this article is to find out the causes of stress among employees in production organizations, and to point out appropriate measures. The aim of the article is to find out whether employees in production organizations experience stress on a daily basis and to investigate the measures that employees consider to be the most appropriate for the purpose of preventing stress.Method: We used a qualitative research method, more precisely a descriptive method, and processed the obtained qualitative data with the online program Atlas.ti.Results: In the article, we identified the causes of stress in production organizations. We also identified the persons responsible for the stress and analyzed the interviews with the help of the Atlas.ti program. We found that employees experience stress differently and act against it in different ways.Organization: With the information obtained from the article, organizations can determine how they can influence employee awareness, how stress affects their well-being, health, job satisfaction and efficiency.Society: This article provides an insight into the most common causes of stress in the workplace, which have a negative impact on the work process, employee efficiency and organizational climate. The results of the article can be used by managers at all levels who want to further explore the topic in their work units.Originality: The originality of the article lies in the fact that it was carried out in the field of production organization. Many studies have already been carried out on the research topic. In the article, we focused primarily on the causes of stress in one production organization in the SE region of Slovenia, and we also list measures against stress.Limitations/Future Research: The limitations of the article can be seen in the fact that we analyzed only one production organization in the SE region of Slovenia. For further research, it would be reasonable to expand the research to several production organizations, which would include all workplaces in different regions of Slovenia, as the existing results cannot be generalized to all production organizations.
Keywords: stress; employees; production organization; causes of stress; measures to prevent stress